Answer:
5a
Step-by-step explanation:
Solution
verified
Verified by Toppr
We have x
3
−ax
2
+6x−a
Apply remainder theorem
x−a=0
x=a
Put x=a in equation.
(a)
3
−a(a)
2
+6a−a
=a
3
−a
3
+6a−a
=6a−a
=5a
Then reminder is 5a
Step-by-step explanation:
464.5cm³
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
.
<h3>
Answer: 70.9%</h3>
Work Shown:
56/79 = 0.70886 approximately
Move the decimal point 2 spots to the right to go from 0.70886 to 70.886%
That rounds to 70.9%
Divide both sides by -12
X=72/-12 now let's simplify 72/-12 = -72/12 so x= -72/12 simplify 72/12= 6
X= -6
Answer:31500
Step-by-step explanation:hope it helps!